Influence of Nitrogen Flow Rate on Properties of TiAlN Thin Film Prepared by Reactive DC Magnetron Sputtering - Rukkun, Jariyaporn; Wongpisan, Witthawat; Waree, Kirati; Aiempanakit, Kamon (Burapha Science Journal, 2026)
In this paper, Titanium aluminium nitride (TiAlN) thin films were deposited on Si substrates by reactive DC magnetron sputtering. The effects of nitrogen gas flow rates on the crystal structure, surface morphology, surface roughness, and hardness of TiAlN films were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), atomic force microscope (AFM) and nanoindenter test, respectively. Target voltage was increased as a function of nitrogen gas flow rates and it indicated that transition mode was found in the range of 0.4-0.8 sccm while compound mode was found over 0.8 sccm. The XRD result showed that crystal structure of TiAlN thin films was found for nitrogen flow rates of 1.3 and 2.0 sccm with prefer orientation of (200) plane. Moreover, crystallinity, crystalline size, and surface roughness were enhanced via increasing nitrogen flow rates. Hardness of TiAlN thin films was improved from 10.28 to 14.99 GPa with increasing nitrogen flow rates from 0.4 to 2.0 sccm, respectively, corresponding with crystallinity. In addition, elemental composition ratio of TiAlN thin films was confirmed by energy dispersive X-ray spectroscopy (EDS) technique. It was found that elemental composition ratio of N/(Ti+Al) and Ti/Al were 1.17 and 2.3 for nitrogen flow rates of 2.0 sccm. These variables were important for the crystal structure and hardness. The resulting hardness was more similar to TiN than TiAlN because the prepared film has twice atomic proportion of titanium than aluminum.